High strain rate and high temperature mechanical response of additively manufactured alloy 625. (September 2022) - Lewis, Jonathan; Pasco, Jubert; McCarthy, Thomas; Chadha, Kanwal; Harding, Matthew; Aranas, Clodualdo
Abstract: Alloy 625 is an important alloy in many industries, including aerospace, providing good mechanical properties in high temperature and corrosive environments. It also retains good properties when additively manufactured using Laser Powder Bed Fusion (LPBF). The LPBF process introduces complex heating and cooling cycles in the material used, thereby affecting the mechanical properties. As a result, existing constitutive models for alloy 625, are not applicable for the LPBF-fabricated material. Therefore, this study sought to establish appropriate constitutive models to simulate the mechanical response of LPBF-fabricated alloy 625 in the desired range of conditions for aerospace applications: high strain rates and temperatures. This was completed by compressing the samples at two strain rates, 700 s −1 and 1700 s −1, and temperatures ranging from 298 K to 773 K using a Split Hopkinson Pressure Bar (SHPB). The information gained from the models was reinforced with micrographs and electron backscatter diffraction (EBSD) images to examine the microstructure of alloy 625 after LPBF. The results from the SHPB testing were then used to calculate the coefficients for five constitutive models, the Johnson-Cook model, a modified Johnson-Cook model, the Hensel-Spittel model, a modified Hensel-Spittel model, and a modified Zerilli-Armstrong model. The Average Absolute Relative Error (AARE) of these models was calculated, and it was determined that the modified Zerilli-Armstrong model had the lowest AARE of the models used, 2.88 % for as-printed alloy 625 and 2.71 % for heat-treated alloy 625.